PTEN expression is consistent in colorectal cancer primaries and metastases and associates with patient survival. (10th June 2013) - Atreya, Chloe E.; Sangale, Zaina; Xu, Nafei; Matli, Mary R.; Tikishvili, Eliso; Welbourn, William; Stone, Steven; Shokat, Kevan M.; Warren, Robert S.
Abstract Phosphatase and tensin homologue deleted on chromosome 10 (PTEN) negatively regulates the phosphoinositide‐3‐kinase (PI3K) signaling pathway. In colorectal cancer (CRC), observed frequencies of loss of PTEN expression, concordant expression in primary tumors and metastases, and the association of PTEN status with outcome vary markedly by detection method. We determined the degree to which PTEN expression is consistent in 70 matched human CRC primaries and liver metastases using a validated immunohistochemistry assay. We found loss of PTEN expression in 12.3% of assessable CRC primaries and 10.3% of assessable liver metastases. PTEN expression (positive or negative) was concordant in 98% of matched colorectal primaries and liver metastases. Next we related PTEN status to mutations in RAS and PI3K pathway genes (KRAS, NRAS, BRAF, and PIK3CA) and to overall survival (OS). PTEN expression was not significantly associated with the presence or absence of mutations in RAS or PI3K pathway genes. The median OS of patients whose tumors did not express PTEN was 9 months, compared to 49 months for patients whose tumors did express PTEN (HR = 6.25, 95% confidence intervals (CI) (1.98, 15.42), P = 0.0017). The association of absent PTEN expression with increased risk of death remained significant in multivariate analysis (HR = 6.31, 95% CI (2.03, 17.93), P = 0.0023). In summary, PTEN expression was consistent in matched CRC primaries and in liver metastases. Therefore, future investigations of PTEN in metastatic CRC can use primary tumor tissue. In patients with liver‐only metastases, loss of PTEN expression predicted poor OS.